Roasting behavior and enhancing technology of high-titanium pellets - CHEN Xu-ling; LIU Shu; GAN Min; FAN Xiao-hui (工程科学学报, 2016)
The roasting properties and solidification behaviors of high-titanium pellets were studied systematically in this paper.The results show that increasing the content of TiO2 in pellets can lead to a greater difficulty in their roasting process. When the content of TiO2 increases from 10% to 21%,the proper preheating time prolongs from 12 min to more than 26 min,while the strength of roasted pellets still decrease from 2486 N to 1728 N per pellet. The reason is that high-titanium pellets contain high content of FeTiO3,which leads to a lower oxidization velocity of magnetite and a lower pre-oxidization degree. This phenonmenon is further adverse to the growth and connection of haplotypite crystals,which finally worsen the consolidation strength of pellets. By simultaneously adding Na OH and applying the wet-grinding process,the surface energy and surface activity of ore particles increase,which contribute to improving the diffusion of solid phases and generating a small amount of low-melting-point compounds. These improvements are conducive to the diffusion of recrystallization and then facilitate the growth of titanium hematite grains and the enrichment of Ti in Fe2TiO5. As a consequence,the proper preheating time shortens to 16 min and the pellet strength increases to 2141 N per pellet for pellets containling 21% of TiO2.